1987
DOI: 10.1007/bf00464645
|View full text |Cite
|
Sign up to set email alerts
|

Fetal development of the tympanic part of the facial canal

Abstract: We studied human middle ears from Wittmaack's temporal bone collection in the ENT Department of the University of Hamburg. In the 12-week-old fetus, cells from the embryonic middle ear mesenchyme form a tiny semi-circle around the tympanic part of the developing facial nerve. During the following weeks, the production of fibrillar material increases until the facial nerve is surrounded by a dense fibrous semi-canal. Intramembranous ossification starts from ossification centers in the anlage of the membranous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…There is a report in which the authors mentioned that the development of the canal was completed by the age of 4 years from an anatomical and radiological standpoint [13]. Another report mentioned that middle ear inflammation in young children could affect the development of the canal [12]. We showed in this study that no significant difference was observed between the incidence of the facial nerve canal dehiscence in temporal bones with chronic otitis media and that in normal controls.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…There is a report in which the authors mentioned that the development of the canal was completed by the age of 4 years from an anatomical and radiological standpoint [13]. Another report mentioned that middle ear inflammation in young children could affect the development of the canal [12]. We showed in this study that no significant difference was observed between the incidence of the facial nerve canal dehiscence in temporal bones with chronic otitis media and that in normal controls.…”
Section: Discussionmentioning
confidence: 41%
“…In young children, inflammation of the middle ear cavity can affect the development of the canal since the development of the canal continues after birth and is completed by the age of 4 years [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…The facial nerve develops in close association with the developing otic capsule 6,7 . By the 16th week of fetal life, the facial nerve enters the meatal segment closely associated with the superior vestibular nerve and surrounded by cartilage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the labyrinth undergoes endochondral ossification, part of the facial canal becomes bone. However, final closure of the nerve in a bony canal depends on the intramembranous ossification of the fibrous connective tissue investing the facial nerve 7 . Closure of the facial canal occurs at about 22 to 25 weeks of gestation, as two ledges of osteoid deposited by osteoblasts with an intervening aplastic zone, until the enclosure is complete.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In normal development, the base of the facial canal is the otic capsule itself, and a thin condensation of mesenchyma surrounds the lateral side of the nerve (1). This is the first appearance of the facial canal.…”
mentioning
confidence: 99%